Muscle Energy Technique Efektif pada Pasien Nyeri Musculus Upper Travezius - Suharto Anwar; Sri Saaadiyah Leksonowati; Hasnia Ahmad; Arpandjaman Arpandjaman (Yayasan Literasi Sains Indonesia, 2023)
Neck pain radiating to the upper trapezius muscles can interfere with the patient's daily activities due to the limited range of motion of the neck, the cervical extensors and flexors become tense due to changes in cervical biomechanics and generally affect workers who require repetition of movements coupled with high work speeds. If you hold your head down for too long it will cause muscle tension or spasm in the neck area and there will be limited neck movement so that the neck is functionally disturbed. The purpose of this study was to determine the effectiveness of muscle energy techniques in neck muscle pain, spasm of the upper travezius muscles. The design of this study was experimental with a pre test-post test one group design. The research subjects met the criteria, namely neck pain myofascial trigger point of the upper trapezius muscle, men and women with moderate to severe pain intensity, willing to be respondents and no musculoskeletal disorders. This research was conducted in June-July 2018. 10 patients with upper trapezius pain (age 21-23 years) were given muscle energy techniques with minimal isometric contractions and stretching 3 times/week, isometric movements repeated 5 times and stretching on the upper trapezius for 45 second. Pain was measured with a Visual analog scale at the beginning and end of the intervention. The results of the study found a significant reduction in pain with scores (p <0.05). The conclusion of this study is that muscle energy technique is effective in reducing pain in cases of spasm of the upper travezius muscle.